UNSCOM's work to uncover Iraq's illicit biological weapons program: A primer. (4th July 2021) - Black, Stephen; Wilson, Henrietta; Lentzos, Filippa
ABSTRACT: In this article, the authors offer a short primer that outlines UNSCOM's historical context and the logistics of its work – central aspects contributing to the Special Commission's successes in searching for Iraq's hidden biological weapons program.